2004
DOI: 10.1002/ajim.10342
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of pure mica pneumoconiosis associated with Sjögren syndrome

Abstract: Pure mica pneumoconiosis can be identified by specific radiologic and pathologic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Sjögren's syndrome is accompanied by various pulmonary diseases 1,5–7 . Because subclinical Sjögren's syndrome can be difficult to diagnose, it is important to detect this syndrome by Saxon's test when investigating various pulmonary diseases 7 …”
Section: Discussionmentioning
confidence: 99%
“…Sjögren's syndrome is accompanied by various pulmonary diseases 1,5–7 . Because subclinical Sjögren's syndrome can be difficult to diagnose, it is important to detect this syndrome by Saxon's test when investigating various pulmonary diseases 7 …”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that mica dust can cause pneumoconiosis [37], characterized by nodular and reticular infiltrates especially in the lower lung fields.…”
Section: Discussionmentioning
confidence: 99%
“…However, such fibrotic patterns were unlike concentric fibrosis, as observed mostly in silicosis. 4,5 The use of advanced physicochemical analytical techniques, such as scanning electron microscopyenergy dispersive xray spectroscopy and analytical transmission electron microscopy of biopsy samples and bronchoalveolar lavage samples of patients with occupational exposure, confirmed the particles as pure mica. [3][4][5] One report 5 also showed an unusual autoimmune disease associated with mica pneumo coniosis.…”
mentioning
confidence: 97%
“…It is well established that mica miners and millers are at increased risk of pneumoconiosis and that mica alone is fibrogenic, even in the absence of other potential occupational or environmental hazards, which are known to cause fibrosis. 1,[3][4][5] Mica pneumoconiosis is still considered a rare disease largely because occupational disease outbreaks occurring in the informal labour sector are not usually formally documented. Several studies 1,4 published in the past two decades provide substantial information about micaassociated pneumoconiosis and show that the disease has a complex set of clinical manifestations.…”
mentioning
confidence: 99%
See 1 more Smart Citation